Worldwide water constraints on attainable irrigated production for major crops - Bram Droppers; Iwan Supit; Michelle TH van Vliet; Fulco Ludwig (Environmental Research Letters, 2021)
In order to achieve worldwide food security, there is a focus on sustainable intensification of crop production. This requires sustainable irrigation water use for irrigated croplands, as irrigation withdrawals are already resulting in groundwater exploitation and unmet ecosystem water requirements. Our study aims to quantify attainable wheat, maize, rice and soybean production on currently irrigated cropland under sustainable water use. Attainable production accounts for increases in nutrient application, while limiting irrigation withdrawals to renewable water availability and without compromising river ecosystem water requirements. Attainable production was quantified using a newly developed two-way coupled hydrological model and crop model. This model framework could comprehensively simulate biophysical processes related to water availability and crop growth under water and nutrient limitations. Our results indicate worldwide crop nitrogen uptake should increase by 20%, to achieve production gap closure. However, worldwide irrigation withdrawals should decrease by more than a third in order to ensure sustainable water use. Under these constraints, a total (all crops) production decrease of 5% was estimated, compared to currently achievable production. Moreover, achievable irrigated crop production in the extensively irrigated croplands of northeastern China, Pakistan and northwestern India would be reduced by up to a third. On the other hand, increases in achievable irrigated crop production may be possible in regions such as southern America, eastern Europe and central Africa. However, in these regions currently only a small fraction of crops is irrigated. Our results imply that intensification on currently irrigated croplands is at odds with sustainable water management, and further locally-oriented research is needed to assess suitable water management options and solutions.